Social work practice in Nigeria: an empowering tool for mass participation in basic education (2008)
The paper presents social work in the presents arrangement with the aim of re-examining and rediscovering its purpose. This effort is being made to reposition social work in Nigeria so as to meet global standards, global challenges and best practices. Some definitions of social work are reviewed, highlighting major comparisons and contrasts. Core purpose and mission statements of social work in Nigeria are examined with particular reference to the Nigeria Association of Social Workers as the professional body, the academic/professional programme of the institution's training social workers and the welfare programme of federal, state and local government as the major employers of social workers in Nigeria. A brief historical survey of social welfare in pre-colonial period was done to enable us know where we were coming from, how we arrived at the present state and consequently prepare for future challenges in social work in Nigeria. This author, is observed that some African social values have been found dispensable in addressing modem social problems and the infusion of these values into the training of social workers in Nigerian cannot be overemphasized. Thereafter, the strengths and limitations of the values are examined with the hope of building on the strengths and diminishing the weaknesses. Finally, the author suggested some steps to be taken by both government and the appropriate bodies in the rediscovering process while preparing to face future challenges.